Techno-economics of rainwater harvesting technology for domestic usage and cooling - Almabruk Shatewi, Abdurahim (2008)
The study on the use of rainwater as a supplementary water supply for residential dwellings was conducted. This study elaborates rainwater harvesting systems that can be applied at residential dwellings with an additional passive cooling system. The analysis was conducted by building a database of rainfall in the test area. The monthly household use was estimated to determine the sizing for the rainwater harvesting system. This analysis was then used to determine the optimum size of the overall rainwater harvesting system. A passive cooling system using rainwater as the cooling agent was designed to reduce indoor temperatures. This passive cooling would contribute to the reduction of the indoor temperatures and the cooling load of the air conditioning system, which will in turn, reduces electrical energy consumption. A proposed cost analysis will be conducted on the prototype system to determine its economic feasibility to be applied at residential dwellings. This economic review will also included the savings from water and electricity bills. These savings will be used to determine the simple payback period on the initial investment to build the systems. From the study we can make some comparisons and conclude the viability of implementing the system in terms of monetary savings and the long term application of a sustainable and renewable source of water.